Experiences of young adults affected by cancer within an 8-week yoga intervention delivered by videoconference: a qualitative interview study - Emma McLaughlin; Nafeel Arshad; Kelsey Ellis; Amy Chen; Kate Fougere; S. Nicole Culos-Reed; Amanda Wurz (Annals of Medicine, 2024)
AbstractBackground Yoga may reduce negative cancer- and treatment-related effects and help improve a range of outcomes, including flexibility, mindfulness, and quality of life among adults affected by cancer. Yet there is little evidence for the role of yoga among young adults (18–39 years) affected by cancer.Purpose The purpose of this study was to explore the experiences of young adults affected by cancer in an 8-week yoga intervention delivered by videoconference.Methods Young adults who were diagnosed with cancer between the ages of 18 and 39 years, at any stage of the cancer trajectory, who were living in Canada, and who completed an 8-week yoga intervention were approached to complete a semi-structured interview. A social constructivist paradigm was adopted. Interviews were transcribed verbatim and analyzed using reflexive thematic analysis.Results Twenty-eight young adults (Mean age = 34.67 ± 5.11 years; n = 25 female) with varied cancer diagnoses participated. Participants’ perspectives were represented across 6 themes: (1) I was juggling a number of challenges and changes throughout the yoga intervention; (2) I noticed some improvements in my mental and physical health; (3) I made time to discover new strategies to take care of myself; (4) I was able to see what my body is capable of; (5) I was held accountable and I appreciated that, and; (6) I was able to be around similar others in a safe (virtual) space.Conclusions Findings suggest that an 8-week yoga intervention may offer some benefits for young adults affected by cancer. Self-care, self-compassion, mindfulness, feelings of physical competence, establishing a routine, and being around similar others were viewed as important components of the intervention and may have contributed to the benefits experienced. Findings underscore the potential utility of yoga as a supportive care intervention for young adults affected by cancer.